The Psychodynamics of Enlightened Leadership Coping with Chaos - Mitroff, Ian I. (Management, Change, Strategy and Positive Leadership, 2021)
This open access book provides a comprehensive look at the pluses and minuses of leadership in times of an unparalleled crisis, such as the COVID-19 global pandemic. It examines the COVID-19 crisis in terms of psychodynamics, crisis management, and especially from the standpoint of complex, messy systems. It analyses how leaders need to think and act differently to cope better with-and potentially prevent-future crises.